The Effect Of Accounting Information Systems On Quality Of Financial Statements (Case Study At Pt Nerounworks Indonesia) - Endang Darmawan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine how the effect of accounting information systems on the quality of financial reports at PT. Neuronworks Indonesia. The research method used is descriptive associative method. The results showed that the accounting information system had an effect on the quality of financial reports at PT. Neuronworks Indonesia.